The Role of Social Assets on Community Well-Being in Urban Farming Project - Zainal, Milah; Hamzah, Siti Raba’ah; M. Z, Rosmiza (Journal of Asian Scientific Research, 2020)
The role of social assets in community well-being in urban farming projects was reviewed in this article. Social assets are one of the key elements in reducing the incidence of poverty as it can affect the income level of an individual or household in a country. In urban farming, it has an important role from the perspective of the urban farmers and its relationship with other individuals or agencies seen as the motivational and adhesive forces for communitarian work that benefits the agriculture development in urban areas. However, previous studies that looked at social asset issues are still lacking in Malaysia, especially in urban farming context. Therefore, this study reviews how social asset benefits in urban farming and its roles in improve community well-being among urban farmers. The findings of the analysis of past studies have contributed roles include knowledge sharing, input and materials access, support community garden development, enhance motivations, technology transfer and adoptions, builds cooperation and encourage good agricultural practice. Since urban agriculture is profitable, more urban farmers should be encouraged to engage in this project. Thus, this study recommends that policies formulated in increasing the urban farmer’s well-being must consider social assets. Future research is needed to study the community farming experience in Malaysia and to understand the factors social assets on their well-being. In this way, the information obtained will be important as a reference to the local community in Malaysia.